Sex Determination Based on Finger Bones: A Systematic Review: Penentuan Jenis Kelamin Berdasarkan Tulang Jari: Tinjauan Sistematis - ur Rahman, Ateeq; Kristianto, Sonny; Widodo, Wimbuh Tri; Rayditya Milanio, Roderikus; ur Rahman, Anees; Setiawardani, Alvina; ul Haq, Ihtisham (Medicra (Journal of Medical Laboratory Science/Technology), 2025)
Sex determination is a crucial step in forensic investigations, particularly when skeletal remains are incomplete. This study aims to evaluate the accuracy of using finger bones as indicators of sex through a systematic review approach. The literature selection followed PRISMA guidelines, with data retrieved from PubMed and Google Scholar using relevant keywords. Out of 95 identified articles, only 10 met the inclusion criteria and were further analyzed. Findings indicate that the length and proportion of finger bones—especially the ring and little fingers—differ significantly between males and females. Classification accuracy based on phalangeal and metacarpal measurements ranged from 80% to 94%. Additionally, hormonal influences such as testosterone contribute to these morphological differences. These results support the effectiveness of finger bones as an alternative method for sex estimation, particularly when pelvis or skull bones are unavailable in forensic contexts.